(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses how social capital has been shaped throughout human history by various natural, historical, socio-economic, political, and spiritual factors. It also addresses the foundation of social capital, which is built on trust, cooperation, mutual assistance, and social relationships among members of society.